Exploring Two Types of Aggressive Behavioural Risk Factors among Illegal Motorcycle Street Racers in Malaysia - Hussin, Zalmizy; Ahmad, Siti Rohana (International Journal of Criminology and Sociology, 2021)
Illegal motorcycle street racing is a threat to civil society – it is a symbol of adolescents’ inner rebellion who channelled their unfulfilled desire through aggressive behaviour on the road, causing significant social and economic impact. Aggressive behaviours have been associated with prohibited substances intake, lack of religious knowledge, problematic family structures, and school failure. In this qualitative study, abductive strategies oriented to phenomenological approaches were employed to assess two types of aggressive behaviour risk factors, which were substance abuse and problematic family structures. In-depth interviews were conducted with thirty people in Penang, Malaysia, who participated in illegal street racing, referred to as Mat Rempits. Their responses were analysed using the NVivo software version 12. The results demonstrate three subthemes to prohibited substances intake: to relieve stress, for personal enjoyment, and for racing purposes, whereby the drugs are taken before races for the riders to be more courageous, aggressive, and agile manoeuvring the motorcycles. Meanwhile, the risk factor of family problems includes divorced and conflicted parents, raised by violence, being neglected, and not being appreciated by the family. Most of the participants stated that growing up with violence caused a psychological impact on their soul, making them stubborn, rude, and aggressive. The results demonstrate the need for a specific intervention programme for the adolescent to reduce their involvement in illegal street racing and aggressive behaviour.